Study on the potential of utilizing rice husk as biosorbent for humic substance - Sharifah Nurul Fazilla, binti Ghazali (Universiti Malaysia Sarawak (UNIMAS), 2013)
Nowadays, consumers concern about the quality of water that being supplied in order to ensure the water supplied is free from any harmful substances like Humic Substances (HS). HS are divided into three main fractions which are Humic Acid, Fulvic Acid, and Humin. High concentration of Humic Acid in drinking water can cause disease for human like stomach cancer. Thus, it is important to develop a new technique to improve the quality of drinking water. Therefore, adsorption method is the best way that can be used in order to remove HS. Moreover, from the previous research, activated carbon has been used to remove HS but it is costly. As an alternative way, Rice husk has been used as an adsorbent in the wastewater treatment compared to other agricultural waste due to its structure and characteristics as adsorbent. Heating and utilization of chemical modifier like Poly (Acrylamide) Carboxyl Modified and Potassium Carbonate can have a significant impact on adsorption of HS. The result has shown that rice husk which is treated with Poly (Acrylamide) Carboxyl Modified occurs the highest rate of adsorption of HS because the Percentage of Transmittance (%) of Carboxylic functional groups decreases as well as the presence of Amine groups in the wastewater. However for Aromatic groups, untreated rice husk become the best adsorbent for HS.